Factors influencing the response to therapy in dogs with eosinophilic bronchopneumopathy - De Simoi, Vanessa; Ballhausen, Bianca Désirée; Proksch, Anna-Lena; Müller, Ralf; Zablotski, Yury; Schulz, Bianka (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
Objectives Canine eosinophilic bronchopneumopathy (EBP) is a poorly understood disease characterized by chronic inflammation of the lower airways. To date, factors affecting the course of the disease are largely unknown. The objective of this study was to investigate the influence of clinical, laboratory, and environmental factors on therapeutic outcome in dogs with EBP.Material and methods Environmental and housing conditions, course of disease, and response to treatment were evaluated using a standardized questionnaire for owners of 29 dogs diagnosed with EBP from 3 different veterinary referral centers in Germany. Data of diagnostic tests (hematology, radiographs, bronchoalveolar-lavage-fluid-(BALF) cytology) were retrospectively obtained from medical records. The influence of the different factors was assessed using Fisher's-exact-test and Mann-Whitney-U- or Kruskal-Wallis-test.Results The proportion of neutrophilic granulocytes in BALF-cytology was significantly higher in dogs with persistent clinical signs compared to dogs that achieved clinical remission (p=0.029). Duration of clinical signs before treatment was significantly longer in dogs with persistent clinical signs (16±12 months) compared to dogs that achieved clinical remission (6±7 months) (p=0.017).Conclusion Early diagnosis and therapy have a decisive influence on the success of treatment.Clinical relevance Dogs with respiratory signs suspicious for EBP should be evaluated in a timely manner to increase the likelihood of clinical remission with an early start of therapy.
Keywords: EBP; cough; eosinophilic lung disease; therapy success